Real-time Classification of Non-Weight Bearing Lower-Limb Movements Using EMG to Facilitate Phantom Motor Execution: Engineering and Case Study Application on Phantom Limb Pain - Lendaro, Eva; Mastinu, Enzo; Håkansson, Bo; Ortiz-Catalan, Max (Frontiers in Neurology, 2017)
Phantom Motor Execution (PME) facilitated by Myoelectric Pattern Recognition (MPR) and Virtual Reality (VR), is positioned to be a viable option to treat Phantom Limb Pain (PLP). A recent clinical trial using PME on upper-limb amputees with chronic intractable PLP, yielded promising results. However, further work in the area of signal acquisition is needed if such technology is to be used on subjects with lower-limb amputation. We propose two alternative electrode configurations to conventional, bipolar, targeted recordings for acquiring surface electromyography (sEMG). We evaluated their performance in a real-time MPR task for non-weight-bearing, lower-limb movements. We found that monopolar recordings using a circumferential electrode of conductive fabric, performed similarly to classical bipolar recordings, but were easier to use in a clinical setting. In addition, we present the first case study of a lower-limb amputee with chronic, intractable PLP treated with Phantom Motor Execution. The patient’s Pain Rating Index dropped by 22 points (from 32 to 10, 68%) after 23 Phantom Motor Execution sessions. These results represent a methodological advancement and a positive proof-of-concept of Phantom Motor Execution in lower limbs. Further work remains to be conducted for a high-evidence level clinical validation of Phantom Motor Execution as a treatment of PLP in lower-limb amputees.